Designing Living Lab Area With Sustainable Architecture Concept - Fariz Harindra Syam; Dara Wisdianti; Suryani Sajar; Saiful Bahri (International Forum of Researchers and Lecturers, 2023)
Educational and research facilities are important for a university. Universitas Pembangunan Panca Budi (UNPAB) wants to provide the best educational and research facilities for its academic community. Living lab and Industrial Park is one of the facilities that UNPAB wants to provide and will greatly support educational and research activities within the university. Based on this, a good Living Lab and Industrial Park area masterplan is needed to create an efficient area. The concept offered in the planning of the Living Lab and Industrial Park Area is Tropical Sustainable while still considering local cultural values. The facility plans provided are livestock areas, agricultural and plantation areas, product processing areas, sports facilities areas, management offices, and ecotourism areas. The living lab and industrial park area is expected to become a superior educational and research facility and can be a producer of products and innovations of UNPAB academics and researchers.